1995
DOI: 10.1148/radiology.195.2.7724778
|View full text |Cite
|
Sign up to set email alerts
|

U.S. screening mammography services with mobile units: results from the National Survey of Mammography Facilities.

Abstract: Mobile mammography facilities compare favorably with stationary facilities. The use of these mobile units in the United States, however, has been limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Mammography facilities are concentrated in urban areas [8], and mobile facilities are underntilized to reach women in rural and innercity areas. Women with less income or education are less likely to get a mammogram.…”
Section: Screeningmentioning
confidence: 99%
“…Mammography facilities are concentrated in urban areas [8], and mobile facilities are underntilized to reach women in rural and innercity areas. Women with less income or education are less likely to get a mammogram.…”
Section: Screeningmentioning
confidence: 99%
“…These differences could have an impact on screening outcomes but there are few studies comparing the performance of mobile units to fixed sites. 10,11 These studies focussed primarily on comparing costs and other elements (price, access, quality assurance). In some studies, screening results for mobile units were reported but were not compared to fixed centres.…”
mentioning
confidence: 99%
“…7 Mobile facilities often encourage self-referred women to obtain screening. A recent survey found that 42% of mobile facilities accept self-referred women.…”
mentioning
confidence: 99%
“…8 These facilities provide screening at reduced cost and with more convenient appointment times and locations than fixed-site facilities. 7 Trained technicians supervise screening, as radiologists are usually not present. Films are read within a few days, and the women are contacted by either mail or telephone if they need further evaluation.…”
mentioning
confidence: 99%
See 1 more Smart Citation